Pemikiran Ibnu Qayyim Al-Jauziyyah Tentang Wali Mujbir dalam Pernikahan (Perspektif Hak Asasi Anak) - Ahmad Rasyid (Jurnal Studi Agama dan Masyarakat, 2016)
One of the major contributions of Ibn Qayyim is about wali mujbir guardian in marriage. He expressed a parent or guardian should not be married off forcibly if it is not accompanied with the consent and approval of the child. This perspective is different from the scholarly (the majority of scholars) that states a parent or guardian may be married off forcibly although without the consent and approval of the child. This study is a literature study (library research) using a contextual approach presented in descriptive and deductive. Data were analyzed through content analysis and hermeneutic methods and study uṣul fiqh. Results from this study: (1) Especially girls (as well as boys) should not be forced to marry and must not be married except with his/her agreement. (2) The Method used legal istinbāt. (3) Relevance thought Ibn Qayyim Al-Jawziyya about mujbir guardian in marriage (a child’s right perspective) in accordance with the spirit of child rights and relevant to contemporary conditions. Thought Ibn Qayyim are considered able to accommodate the growing problems of law in society in order to avoid forcing the parents to their children to marry without first requested permission and consent of the child.